2021
DOI: 10.3390/su13179805
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Higher Education Institutions in the Implementation of Circular Economy in Latin America

Abstract: Circular economy (CE) describes a sustainable alternative approach to the current linear economy system. It is a growing topic among scholars, practitioners, and decisionmakers; it encompasses several concepts related to sustainability and requires the synergy of multiple actors for success, including higher education institutions (HEIs) as one of the most relevant ones. Current CE is based mostly on experiences in Global North developed countries, where the concept has gained great attention and has already i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 259 publications
0
10
0
2
Order By: Relevance
“…Therefore, the industry needs to increase its knowledge and technical know-how ameliorating the producing methodologies and utilizing the biomolecules' content of the releasing by-products adopting the circular economy approach [116]. Thus changing the way of producing, consuming and living, it will be possible to deliver a zero-plastic pollution and waste, reducing carbon emissions and helping to boost and drive a circular bio-economy capable to safeguard the environment and combat the climate change [117][118][119][120][121][122][123]. Circular bio-economy, in fact, based on nature-based goods, recycling materials and investments in green initiatives by the power of bioscience and biotechnology, might represent a solution to address the resources scarcity and help to tackle the air and marine pollution [118][119][120][121][122].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the industry needs to increase its knowledge and technical know-how ameliorating the producing methodologies and utilizing the biomolecules' content of the releasing by-products adopting the circular economy approach [116]. Thus changing the way of producing, consuming and living, it will be possible to deliver a zero-plastic pollution and waste, reducing carbon emissions and helping to boost and drive a circular bio-economy capable to safeguard the environment and combat the climate change [117][118][119][120][121][122][123]. Circular bio-economy, in fact, based on nature-based goods, recycling materials and investments in green initiatives by the power of bioscience and biotechnology, might represent a solution to address the resources scarcity and help to tackle the air and marine pollution [118][119][120][121][122].…”
Section: Discussionmentioning
confidence: 99%
“…Thus changing the way of producing, consuming and living, it will be possible to deliver a zero-plastic pollution and waste, reducing carbon emissions and helping to boost and drive a circular bio-economy capable to safeguard the environment and combat the climate change [117][118][119][120][121][122][123]. Circular bio-economy, in fact, based on nature-based goods, recycling materials and investments in green initiatives by the power of bioscience and biotechnology, might represent a solution to address the resources scarcity and help to tackle the air and marine pollution [118][119][120][121][122]. Thus consumers education together with industry research and innovation represent the key to transitioning from a plastic-based economy to a bio-based ones, by changing the production of feedstock and non recyclable petrol-based materials in favor of degradable fossil-free goods, medical devices and cosmetics [124][125][126][127].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half of the respondents indicated that they wanted more information on this matter during their studies. Universities, as part of a global academic community with shared values, should engage with the global challenges of today [49,50]. These institutions play a key role in shaping the worldview and knowledge of the younger generation [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…A higher share of economic activities is related to repairing, reusing, or sorting waste, and thus, advantages for the transition to a circular economy may already exist. Circular economy needs to be integrated with collaborative, bottom-up, and innovative dynamics since it has a great potential for contributing to local and inclusive development efforts [81]. The COVID-19 pandemic in Argentina and other Latin American countries revealed significant shortcomings in the linear economy; the vulnerability of global value chains, the depletion of natural resources, and the exacerbation of social inequalities.…”
Section: Food Sovereignty and Sustainability Problems In Rural Commun...mentioning
confidence: 99%